Parties, elections and electoral contests : competition and contamination effects - Guinjoan i Cesena, Marc, 1985- (Ashgate, 2014)
According to the Duvergerian theories, in the long run, only viable parties are expected to stand for elections. Non-viable parties should join a pre-electoral coalition with another party or withdraw from competition entirely. Why then do non-viable political parties throughout the world systematically continue presenting candidates? This book argues that political parties will take advantage of their viability in an arena to present candidacies in other arenas where they do not have chances to become viable.